ANNUAL CHANGES OF BEACH PROFILE AND NEARSHORE SEDIMENT DISTRIBUTION OFF DUNGUN-KEMAMAN,TERENGGANU, MALAYSIA (Jurnal Teknologi (Sciences & Engineering), 2018)
A proper understanding of beach processes must include the adjacent shallow marine waters or nearshore environment. This paper focused on the sedimentological and morphological investigation of Terengganu coastal area stretch lies between Dungun and Kemaman. The study area comprised five beaches and 36 nearshore stations. The present investigation attempts to study the time variation of the grain-size along the coast and in order to observe one-year cycle of the perpendicular profile of the beach. Teluk Lipat beach faced a huge modification compared to other beaches. The severely-eroded beaches in the study area characterized by coarse sand. Sediments from backshore and upper beach zone decreased in mean size and became poorly sorted towards surf zone area. Meanwhile, superficial sediment distribution of nearshore area revealed that silt is the most dominant component and the sediment size became coarser towards the shoreline. The results favor an alternative explanation, indicating that the river is the main source for the coastal sands, which are probably reworked by longshore currents on opposite directions apart from the river mouth, resulting on coastal propagation.